(untitled) (Research, Society and Development, 2021)
Alternative methodologies for teaching and learning have stood out in the teaching of anatomy. Because it allows the student to take an active role in the learning process, which is what education seeks by discovery, thus seeking to overcome the limitations of teaching. To systematically review in the literature, the teaching methods most used in anatomy, a search was performed in the PubMed databases. Original articles that worked on human anatomy in face-to-face higher education were included, if they dealt with the teaching-learning process using alternative educational models. 180 articles were found at the intersection of the following descriptors: “human anatomy”, “higher education”, “teaching” and “educational models”; of which 26 were selected. The analyzed studies demonstrated the lack of continuity in research on the use of alternative methods in teaching anatomy, and that most of these published works are from international institutions. Of the teaching methods cited in the studies, they were varied, mostly involving the active methodologies. The teaching methods of cadaveric dissection and 3D impressions stood out when compared to other teaching alternatives. Therefore, the studies identified on alternative methodologies for teaching human anatomy indicate the efficiency of these methods as they stimulate student satisfaction with the discipline and significant learning.